The Importance of Bottomland Hardwood Forests for Wildlife - Holly K. Ober (EDIS)
WEC271, a 7-page illustrated fact sheet by Holly K. Ober, discusses the importance of seasonally flooded forests located along waterways, plants and wildlife of bottomland forests, and how to manage them for wildlife. Includes additional sources of information. Published by the UF Department of Wildlife Ecology and Conservation, November 2009.